2020
DOI: 10.1093/cid/ciaa1737
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Attack Rate and Family Clustering of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in Children of Healthcare Workers With Confirmed Coronavirus Disease 2019 (COVID-19)

Abstract: We measured serum SARS-CoV-2 antibodies in 215 children of healthcare workers to estimate secondary attack rates (SAR). Twenty-one families had a parent with confirmed COVID-19. There was strong evidence of family clustering (P<0.001): 20/21 (95.2%) children were seropositive in 9 families and none of 23 children in 12 other families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Our observation of a SAR ≈10 percentage points higher in adults than in children is consistent with household studies based on RT-PCR-confirmed SARS-CoV-2 infection (10). In contrast, previous household transmission studies based on SARS-CoV-2 serologic testing reported lower (18), similar (28%) (17), or higher (43%-52%) (19)(20)(21) SARs in children. However, these studies were relatively small.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observation of a SAR ≈10 percentage points higher in adults than in children is consistent with household studies based on RT-PCR-confirmed SARS-CoV-2 infection (10). In contrast, previous household transmission studies based on SARS-CoV-2 serologic testing reported lower (18), similar (28%) (17), or higher (43%-52%) (19)(20)(21) SARs in children. However, these studies were relatively small.…”
Section: Discussionsupporting
confidence: 89%
“…Previous household transmission studies found SARS-CoV-2-specific IgG in 28% (17), 34% (18), 42% (19), 45% (20) and 52% (21) of exposed children; SARs were lower (18), similar to (17,21), or higher (19) than in exposed adult household members. However, the low number of studied households with children (21-130 households) (17)(18)(19)(20)(21) was a limitation.…”
mentioning
confidence: 76%
“…Anecdotally, husbands and wives, siblings, and adult parents and children are not infrequently hospitalized in succession, though the prevalence of this is unknown. An inoculum effect may underlie this finding [31] and also explain why secondary cases in households appear to be overdispersed, with either most or all members infected, or none at all [6,32,33]. Viral load dynamics will no doubt continue to shape household transmission and the larger pandemic, as newer, potentially more infectious variants emerge even as vaccination decreases the “community viral load.”…”
Section: Discussionmentioning
confidence: 99%
“…In our formulation, R G = p and f h is h multiplied by the secondary attack rate within households. We use the estimated secondary attack rate from UK data, which varies between 0.25 for large household sizes and 0.49 for households of size 2 [ 15 , 16 ]. Furthermore, below the percolation threshold, R H < 1 because the infection is necessarily limited to small, disconnected clusters.…”
Section: Methodsmentioning
confidence: 99%